2023
DOI: 10.3389/fvets.2022.1075133
|View full text |Cite
|
Sign up to set email alerts
|

Exploring broilers and native fowls of Andaman and Nicobar Islands as a source of β-lactamase-producing Enterobacteriaceae even with limited anthropogenic activities and docking-based identification of catalytic domains in novel β-lactamase variants

Abstract: ObjectivesThe present study was conducted to detect the occurrence of β-lactamase and biofilm-producing Escherichia coli, Salmonella, and Klebsiella in broilers and native fowl reared in the Andaman and Nicobar Islands, India. The study also included molecular docking experiments to confirm the nature of the catalytic domains found in the β-lactamase variants obtained and to reveal the clonal relationship of the isolates with human clinical strains from the database.Materials and methodsA total of 199 cloacal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The metagenomic sequencing showed that the abundance of sulphonamide and fluoroquinolone resistance genes decreased compared with that in measurements by [1,4,27]. Compared with [2,3,28]'s measurements, the abundance of glycopeptide resistance genes and AdeF and qacG multidrug resistance genes was high, indicating that the Chinese government's policy of reducing and replacing antibiotics in animal husbandry has played a role in altering the abundances of antibiotic resistance genes. The existence of multiple drug-resistant gene phenotypes in wastewater from livestock and poultry farms and drinking water reservoirs has raised public health concerns.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The metagenomic sequencing showed that the abundance of sulphonamide and fluoroquinolone resistance genes decreased compared with that in measurements by [1,4,27]. Compared with [2,3,28]'s measurements, the abundance of glycopeptide resistance genes and AdeF and qacG multidrug resistance genes was high, indicating that the Chinese government's policy of reducing and replacing antibiotics in animal husbandry has played a role in altering the abundances of antibiotic resistance genes. The existence of multiple drug-resistant gene phenotypes in wastewater from livestock and poultry farms and drinking water reservoirs has raised public health concerns.…”
Section: Discussionmentioning
confidence: 90%
“…The interconnected domains of the One Health Framework have identified that the emergence, evolution, and dissemination of antibiotic-resistant microorganisms at both the local and global scales pose a substantial risk to global health. Multiple environmental reservoirs of microorganisms, including water and farm waste, contribute to the dissemination of ABR [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and other pathogens shedding antimicrobial resistance are zoonotic, i.e. infecting both humans and other animal species [105][106][107][108][109]. WES for zoonotic pathogens may require a comprehensive One Health approach in designing the surveillance scheme, interpreting results, and planning management actions [38,86,110].…”
Section: One Health Perspective For Waterborne Pathogensmentioning
confidence: 99%
“…and other pathogens shedding antimicrobial resistance are zoonotic, i.e. infecting both humans and other animal species [105][106][107][108][109]. WES for zoonotic pathogens may require a comprehensive One Health approach in designing the surveillance scheme, interpreting results, and planning management actions [38,86,110].…”
Section: One Health Perspective For Waterborne Pathogensmentioning
confidence: 99%